BNF 69 : British national formulary. (London : Pharmaceutical Press, 2015)
This biannual publication provides details on all medicines currently available on the UK market, with particular reference to their uses, contraindications, side effects, dosage and relative cost.
Includes bibliographical references and index.
Keywords: Formularies as Topic; Great Britain; Periodicals